Vertical pelvic movement asymmetry and lameness location in ipsilateral combined forelimb and hindlimb lameness cases - Means, Kari; Hayden, Lyndsey; Kramer, Joanne; McCracken, Megan Jill; Reed, Shannon K.; Wilson, David A.; Keegan, Kevin George (Equine veterinary journal, 2025)
Background Compensatory vertical head and pelvis movement asymmetry may occur in trotting horses with a primary cause of lameness in one end of the body due to the weight shifting between limbs, leading to apparent combined forelimb and hindlimb lameness (CFHL). Little is known about CFHL patterns observed with body‐mounted inertial sensors (BMIS) and regardless of their underlying mechanisms, compensatory and secondary lameness may complicate the definitive identification of the primary causes of lameness. Objective Determine associations between vertical pelvic movement asymmetry and location of primary lameness in ipsilateral CFHL cases where hindlimb lameness is solely impact or push‐off type. Study design Retrospective cohort. Methods From a body‐mounted inertial sensor (BMIS) evaluated equine lameness database, we identified cases with a consistent, low‐variability ipsilateral impact (IpI) or ipsilateral pushoff (IpP) hindlimb lameness in a straight‐line trot and that had definitive diagnoses. Cases were categorised by lameness location to the limb(s), diagnosis, and ratio of the amplitude of forelimb to hindlimb lameness (Forea/Hinda). Differences in the numbers of IpI and IpP cases in these categories were analysed with chi‐square tests, effect sizes, and odds ratios. Results Among the 2375 total lameness cases screened, 49 IpI and 36 IpP cases met the criteria for consistency, low variability, and definitive diagnosis. IpI cases were more likely than IpP cases to have forelimb‐only lameness causes when Forea/Hinda >1 (OR = 43, 95% CI = 2.3–798). IpP cases were more likely than IpI cases to have hindlimb‐only causes at both Forea/Hinda >1.0 (OR = 20, 95% CI = 2.2–200) and <1.0 (OR = 14, 95% CI = 2.9–66.7). Compared with IpI, IpP cases were more frequently diagnosed with tendon, suspensory ligament, or high‐motion joint disorders in hindlimbs (OR = 3.6, 95% CI = 1.1–12.3) and less with unknown causes (OR = 13.2, 95% CI = 3.2–75.2). In IpI cases, positive forelimb regional anaesthesia often reduced hindlimb lameness, whereas in IpP cases, positive hindlimb regional anaesthesia typically lessened forelimb lameness. Main limitations Most cases were Quarter Horses. The likelihood of location and cause of lameness may be different for other breeds. Conclusions The type of pelvic movement asymmetry observed in IpI and IpP cases is linked to the location and underlying cause of the primary lameness.